The Australian Measles Control Campaign, 1998 - Turnbull Fiona M.; Burgess Margaret A.; McIntyre Peter B.; Lambert Stephen B.; Gilbert G. Lyn; Gidding Heather F.; Escott Ros G.; Achat Helen M.; Hull Brynley P.; Wang Han; Sam Greg A.; Mead Cathy L. (The World Health Organization, 2001)
The 1998 Australian Measles Control Campaign had as its aim improved immunization coverage among children aged 1-12 years and, in the longer term, prevention of measles epidemics. The campaign included mass school-based measles-mumps-rubella vaccination of children aged 5-12 years and a catch-up programme for preschool children. More than 1.33 million children aged 5-12 years were vaccinated at school: serological monitoring showed that 94% of such children were protected after the campaign, whereas only 84% had been protected previously. Among preschool children aged 1-3.5 years the corresponding levels of protection were 89% and 82%. During the six months following the campaign there was a marked reduction in the number of measles cases among children in targeted age groups.